Upaya Peningkatan Self Awareness Masyarakat pada Kondisi Stunting di Wilayah Puskesmas Porong Sidoarjo - Rizki, Muhammad Risya; Djunawan, Achmad; Ramadhani, Ratna Amaliya (STIKES Yayasan RS.Dr.Soetomo, 2024)
The issue of nutrition, such as stunting, falls under Sustainable Development Goal (SDG) number 2, which aims to eliminate all forms of malnutrition. Stunting is a serious problem as it can impact cognitive abilities, unbalanced bodily functions, and result in an undesirable body posture. One of the causes of the increasing incidence of stunting, particularly in the Porong Sidoarjo Health Center, is the lack of community understanding about health, especially regarding stunting. The prevalence of stunting in Sidoarjo is 23.9%, and in the Porong Health Center's working area, it is 28%. The objective of this community service is to enhance the self-awareness of the community to address the condition of stunting in the Porong Sidoarjo Health Center. The target audience for this community service activity is mothers of infants and toddlers who are indicated as stunted in the Porong Sidoarjo Health Center's working area. The method of this activity involves counseling with presentations, practical exercises on reading high z-scores for height/weight and weight/age, Q&A sessions, and completing pretest and posttest questionnaires. The results of this community service activity indicate that the majority of participants have experienced an increase in knowledge, particularly regarding the characteristics and impacts of stunting, and have improved self-awareness regarding stunting in infants and toddlers.